Into a brave new world: Haemophilia A & von Willebrand Disease Surgery with novel therapies. (6th May 2022) - Harrison, Catherine; Chase, Jaime; Fawcett, Kathy; Shoemark, Robyn; Valderrama, Yadira
Abstract: Introduction: Haemophilia & von Willebrand disease are both recognised inherited bleeding disorders. With increased access to highly efficient and safe replacement and novel therapies, management of surgical interventions in this group can be safely managed by experienced multidisciplinary teams. Aim: To review the evidence for managing surgery in the era of novel therapies. Method: We explore four cases and establish the role of the clinical nurse specialist within the surgical pathway. Results: All of these cases evidence the continued important role of both the multidisciplinary planning prior to any surgical interventions in people with bleeding disorders and the key role of the Nurse Specialist in ensuring this plan is then implemented. Key focuses of communication with all parties involved in the patient journey, performing education for the patient, family and wider healthcare team about the underlying bleeding disorder and the importance of time critical medicines being given on time is essential. Conclusion: These cases demonstrate that individuals with bleeding disorders are at risk of developing other rare conditions alongside their life long condition, in addition to comorbidities associated with ageing. Evidence for rare plus rare is likely to be minimal as demonstrated within the cases, and recognition of how to reach out to international peers in the field is important. Sharing complex case management at national & international meetings and in publication has never been so important. Abstract : Visual summary